Tsetse flies as tools for minimally invasive blood sampling - Alexandra Habicher; Udo Feldmann; Lydia Kolter; Gunther Nogge (Wildlife Society Bulletin)
Abstract Collecting blood samples is an important aspect of wildlife studies where data on physiological parameters are required. To avoid stress to the test animals and its potential influence on the test parameters, minimally invasive blood sampling offers numerous advantages. Here, we describe using the African tsetse fly (Glossina brevipalpis) to sample blood from meerkats (Suricata suricatta) habituated to human presence. Prior to the experiments, test animals were trained with positive reinforcement to tolerate a box that enclosed the insects being attached to their neck. This method allows drawing blood samples at defined points of time and from specific individuals during captive studies. Additionally, because it presents the first example of an African haematophagous insect suitable for sampling blood, African field studies might benefit from this minimally invasive blood‐sampling technique without the risk of importing potentially invasive species. © 2013 The Wildlife Society.